Degradation of lead (Pb) from car wash waste water sample using ultrasonic assisted extraction process - Noorhidayah, Khamis (2010)
The waste water from the car wash industry is actually containing heavy metals that will affect environment and health. Many researchers have done different ways to degrade heavy metal in the different sources of waste water. In this study, lead (Pb) is the major heavy metal found from the car wash effluent sample. The degradations of this heavy metal use the ultrasonic process which is assisted by the extracting solvent for get higher degradation. Then, the aim of this study was to find the suitable condition of degradation lead (Pb) from car wash waste water with focused on the influence of time sonication, volume solvent and type of the solvents used. Two types of solvent are used in this research which are methanol and acid hydrochloric. Each solvent was mixed with the sample with different volume also the time process. The two condition of treatment was done; by present and absent of ultrasonic treatment. The analysis of sample was using Atomic Absorption Spectrophotometry (AAS) to identify the final lead (Pb) concentration. Result found that the suitable conditions for lead (Pb) degradation were using 3 minutes ultrasonic process and assisted with methanol (MeOH) solvent by the volume 10ml. It was shown that, the higher percentage degradation was achieved by 42.5%. In conclusion, Ultrasound alone was not good enough to degrade the heavy metal itself in waste sample and by an addition of solvent, it was played a role as predominated over that of ultrasonic process enhanced the result performance. The standard condition of process was important to recognize for further commercialized programs.